Pengaruh Online Shop Terhadap Budaya Belanja Masyarakat Perumnas Made Lamongan - Durrotun Nafisah; Ahmad Sidi; MACHSUNNAH YAYUK CHAYATUN; Mohammad Lazim Fahrudin (Academia Publication, 2021)
The purpose of this study is to find out which online shops have an effect on the shopping culture of the Made Taman community in Made Taman Village, Lamongan Regency in 2020. In this study the researchers chose to use quantitative methods. The population in this study were adolescents or adults aged 20 years to 40 years who resided in Made Taman north and south in 2020 in Made Village, Lamongan district, totaling 48 respondents. The test technique uses simple Linear Regression analysis, the results obtained from the calculation between the value of t count> t table with a significant level of 5%, namely 7,477> 2,012, so it can be concluded that H0 is rejected and H1 is accepted. After getting to know the Online Shop, people more often shop at online stores than traditional markets because the people of Made Taman are very satisfied with the quality given to the online shop and believe shopping at an online shop is the right decision.